Phosphoproteomics reveals novel modes of function and inter‐relationships among PIKKs in response to genotoxic stress - Schlam‐Babayov, Sapir (EMBO J, 2020)
The DNA damage response (DDR) is a complex signaling network that relies on cascades of protein phosphorylation, which are initiated by three protein kinases of the family of PI3‐kinase‐related protein kinases (PIKKs): ATM, ATR, and DNA‐PK. ATM is missing or inactivated in the genome instability syndrome, ataxia‐telangiectasia (A‐T). The relative shares of these PIKKs in the response to genotoxic stress and the functional relationships among them are central questions in the genome stability field. We conducted a comprehensive phosphoproteomic analysis in human wild‐type and A‐T cells treated with the double‐strand break‐inducing chemical, neocarzinostatin, and validated the results with the targeted proteomic technique, selected reaction monitoring. We also matched our results with 34 published screens for DDR factors, creating a valuable resource for identifying strong candidates for novel DDR players. We uncovered fine‐tuned dynamics between the PIKKs following genotoxic stress, such as DNA‐PK‐dependent attenuation of ATM. In A‐T cells, partial compensation for ATM absence was provided by ATR and DNA‐PK, with distinct roles and kinetics. The results highlight intricate relationships between these PIKKs in the DDR.